Magyar peregrinusok kölcsönügylete Erlangenben - Bozzay, Réka (Gerundium, 2011)
The Loan Transaction of Peregrine Students in Erlangen. The sources—four brief documents—made public here offer an insight into student life at the end of the 18th century: the high fees of tuition, especially the cost of their studies abroad, significantly impacted not only on the cost of education but on the subsequent lives of the students as well. The ”peregrine students” were obliged to take loans, the burdens of which they had to carry for long years. Two of the documents here presented pertain to two peregrinators who completed their studies at the College of Debrecen but had earlier concluded a loan agreement in Erlangen, Germany. In the Archives of the Debrecen Protestant College we can read the texts of the original contracts, as well as the written documents submitted to the home church authorities in the matter of the reclamation of the loaned sum.